Le recul du travail des enfants au Québec entre 1940 et 1960: une explication des conflits entre les familles pauvres et l'État providence - Jean, Dominique (Labour/Le Travailleur, 1989)
Abstract In the middle of the 20th century, Quebec and Canadian governments narrowed their control of child labour. This paper attempts to retrieve the effects of the family allowances program of 1945, of the Compulsary School Attendance Law of 1943, and of the labour laws, on family economies and the general manpower, on parental values and public norms. It argues that these legislations played an effective role in the complex phenomenon of the withdrawal of child labour in the province, although in ways not predicted by the state: more than governments it is parents who used the laws, by claiming for their sons and daughters the new rights associated with these measures, thus allowing them to attend school during a longer period.